2019
DOI: 10.1186/s40529-019-0277-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermotolerance evaluation of Taiwan Japonica type rice cultivars at the seedling stage

Abstract: BackgroundThe subtropical rice varieties grown in Taiwan are mainly Japonica-type rice varieties, which are grown in the southernmost- and lowest-latitude Japonica type rice cultivation area in the world. In Taiwan, seedlings that are planted either by transplanting or direct seeding in the second crop will face the season with the highest temperatures during the year. High-temperature stress severely influences early rice growth and causes yield losses. With global warming deteriorating, this problem is becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Further the efficiency of the technique is well explored with limited genotyping panel to arrive at small number of useful markers out of huge tests, for further studies (Gouda et al, 2020). The above outcomes propose that the TIR strategy is an amazing and productive method to recognize hereditary changeability in high temperature resistance in rice inside a brief timeframe and it is appropriate for screening an enormous number of genotypes (Hsuan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Further the efficiency of the technique is well explored with limited genotyping panel to arrive at small number of useful markers out of huge tests, for further studies (Gouda et al, 2020). The above outcomes propose that the TIR strategy is an amazing and productive method to recognize hereditary changeability in high temperature resistance in rice inside a brief timeframe and it is appropriate for screening an enormous number of genotypes (Hsuan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the last few decades, high-temperature stress has become a major environmental stressor that restricts proper growth and yield of crops [ 36 , 37 ], and the promotion of grafting technology provides an opportunity to improve crop resistance to various biotic and abiotic stresses, including high-temperature stress [ 6 ]. In our study, heat stress at 42/32 °C (day/night) significantly prevented the growth of grafted seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that an increase of temperature ranging between 45-53°C decreased the seed viability with no significant effect on seed vigor, whereas temperature higher than 53-55°C reduced seed germination (Lewis Ivey & Miller, 2004). Hot water disinfection for a long time (60°C for 30 min) decreased the germination percentage and emergence of rice varieties (Hsuan, Jhuang, Wu, & Lur, 2019). Seeds of burdock (Prosopis) species treated with boiling ISSN 2166-0379 2020 water increased the germination (Pasiecznik, Harris, Tavares, & Cassama, 1998).…”
Section: Disinfection With Plant Preservative Mixture (Ppm Tm )mentioning
confidence: 98%